(untitled) (Zoological Records and Reviews, 2024)
The Netherlands, despite being one of Europe’s most densely populated and agriculturally intensified countries, harbours a vertebrate fauna whose threatened proportion has increased substantially over the past three decades. This study provides a comprehensive, multi-taxon assessment of the conservation status of threatened vertebrates in the Netherlands, integrating the 2023 Dutch Red List evaluations with population trend data, habitat condition indices, and policy compliance metrics for five vertebrate groups: freshwater fish (n = 38 assessed species), amphibians (n = 18), reptiles (n = 12), breeding birds (n = 184), and terrestrial mammals (n = 68). Of 320 assessed species, 118 (36.9%) qualify as Threatened (Critically Endangered, Endangered, or Vulnerable) under Dutch Red List criteria. Freshwater fish show the highest threatened proportion (60.5% of assessed species), driven by hydrological modification and eutrophication of the Rhine-Meuse delta system. Breeding birds show the greatest absolute decline in the threatened proportion since 1990 (+14.2 percentage points), with farmland birds (Alauda arvensis, Limosa limosa, Vanellus vanellus) constituting the most rapidly declining guild. Habitat condition indices based on Natura 2000 quality assessments were significantly lower for threatened than for non-threatened species across all five groups (Mann-Whitney p < 0.001 in all cases). Species distribution modelling under IPCC RCP 4.5 and 8.5 scenarios projects further contraction of suitable habitat for 74% of currently threatened species by 2050. These findings identify priority taxa and landscape sectors for targeted intervention under the EU Nature Restoration Law (2024/1991) and Dutch National Programme Rural Area.